Assessment of whole-site methane emissions from anaerobic digestion plants: Towards establishing emission factors for various plant configurations - Viktoria Wechselberger; Marlies Hrad; Marcel Bühler; Thomas Kupper; Bernhard Spangl; Anders Michael Fredenslund; Marion Huber-Humer; Charlotte Scheutz (Waste Management, 2025)

The effect of water on alkali trace element diffusion (Li, Rb, Cs) in silicic melts - Juliana Troch; Christian Huber; Nico Kueter; Marcel Guillong; Mike Ackerson; Peter Ulmer; Olivier Bachmann (Geochimica et Cosmochimica Acta, 2024)

Variable detection of Omicron-BA.1 and -BA.2 by SARS-CoV-2 rapid antigen tests - Andreas Osterman; Irina Badell; Christopher Dächert; Nikolas Schneider; Anna-Yasemin Kaufmann; Gamze Naz Öztan; Melanie Huber; Patricia M. Späth; Marcel Stern; Hanna Autenrieth; Maximilian Muenchhoff; Alexander Graf; et al. (Medical Microbiology and Immunology, 2023)
During 2022, the COVID-19 pandemic has been dominated by the variant of concern (VoC) Omicron (B.1.1.529) and its rapidly emerging subvariants, including Omicron-BA.1 and -BA.2. Rapid antigen tests (RATs) are part of national testing strategies to identify SARS-CoV-2 infections on site in a community setting or to support layman’s diagnostics at home. We and others have recently demonstrated an impaired RAT detection of infections caused by Omicron-BA.1 compared to Delta. Here, we evaluated the performance of five SARS-CoV-2 RATs in a single-centre laboratory study examining a total of 140 SARS-CoV-2 PCR-positive respiratory swab samples, 70 Omicron-BA.1 and 70 Omicron-BA.2, as well as 52 SARS-CoV-2 PCR-negative swabs collected from March 8th until April 10th, 2022. One test did not meet minimal criteria for specificity. In an assessment of the analytical sensitivity in clinical specimen, the 50% limit of detection (LoD50) ranged from 4.2 × 10 4 to 9.2 × 10 5 RNA copies subjected to the RAT for Omicron-BA.1 compared to 1.3 × 10 5 to 1.5 × 10 6 for Omicron-BA.2. Overall, intra-assay differences for the detection of Omicron-BA.1-containing and Omicron-BA.2-containing samples were non-significant, while a marked overall heterogeneity among the five RATs was observed. To score positive in these point-of-care tests, up to 22-fold (LoD50) or 68-fold (LoD95) higher viral loads were required for the worst performing compared to the best performing RAT. The rates of true-positive test results for these Omicron subvariant-containing samples in the highest viral load category (Ct values < 25) ranged between 44.7 and 91.1%, while they dropped to 8.7 to 22.7% for samples with intermediate Ct values (25–30). In light of recent reports on the emergence of two novel Omicron-BA.2 subvariants, Omicron-BA.2.75 and BJ.1, awareness must be increased for the overall reduced detection rate and marked differences in RAT performance for these Omicron subvariants.

Impaired detection of omicron by SARS-CoV-2 rapid antigen tests - Andreas Osterman; Irina Badell; Elif Basara; Marcel Stern; Fabian Kriesel; Marwa Eletreby; Gamze Naz Öztan; Melanie Huber; Hanna Autenrieth; Ricarda Knabe; Patricia M. Späth; Maximilian Muenchhoff; et al. (Medical Microbiology and Immunology, 2022)
Since autumn 2020, rapid antigen tests (RATs) have been implemented in several countries as an important pillar of the national testing strategy to rapidly screen for infections on site during the SARS-CoV-2 pandemic. The current surge in infection rates around the globe is driven by the variant of concern (VoC) omicron (B.1.1.529). Here, we evaluated the performance of nine SARS-CoV-2 RATs in a single-centre laboratory study. We examined a total of 115 SARS-CoV-2 PCR-negative and 166 SARS-CoV-2 PCR-positive respiratory swab samples (101 omicron, 65 delta (B.1.617.2)) collected from October 2021 until January 2022 as well as cell culture-expanded clinical isolates of both VoCs. In an assessment of the analytical sensitivity in clinical specimen, the 50% limit of detection (LoD50) ranged from 1.77 × 10 6 to 7.03 × 10 7 RNA copies subjected to the RAT for omicron compared to 1.32 × 10 5 to 2.05 × 10 6 for delta. To score positive in these point-of-care tests, up to 10-fold (LoD50) or 101-fold (LoD95) higher virus loads were required for omicron- compared to delta-containing samples. The rates of true positive test results for omicron samples in the highest virus load category (Ct values < 25) ranged between 31.4 and 77.8%, while they dropped to 0–8.3% for samples with intermediate Ct values (25–30). Of note, testing of expanded virus stocks suggested a comparable RAT sensitivity of both VoCs, questioning the predictive value of this type of in vitro-studies for clinical performance. Given their importance for national test strategies in the current omicron wave, awareness must be increased for the reduced detection rate of omicron infections by RATs and a short list of suitable RATs that fulfill the minimal requirements of performance should be rapidly disclosed.

Correction to: Diagnostic performance of four SARS-CoV-2 antibody assays in patients with COVID-19 or with bacterial and non-SARS-CoV-2 viral respiratory infections - Timo Huber; Philipp Steininger; Pascal Irrgang; Klaus Korn; Matthias Tenbusch; Katharina Diesch; Susanne Achenbach; Andreas E. Kremer; Marissa Werblow; Marcel Vetter; Christian Bogdan; Jürgen Held (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Diagnostic performance of four SARS-CoV-2 antibody assays in patients with COVID-19 or with bacterial and non-SARS-CoV-2 viral respiratory infections - Timo Huber; Philipp Steininger; Pascal Irrgang; Klaus Korn; Matthias Tenbusch; Katharina Diesch; Susanne Achenbach; Andreas E. Kremer; Marissa Werblow; Marcel Vetter; Christian Bogdan; Jürgen Held (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
SARS-CoV-2 antibody assays are used for epidemiological studies and for the assessment of vaccine responses in highly vulnerable patients. So far, data on cross-reactivity of SARS-CoV-2 antibody assays is limited. Here, we compared four enzyme-linked immunosorbent assays (ELISAs; Vircell SARS-CoV-2 IgM/IgA and IgG, Euroimmun SARS-CoV-2 IgA and IgG) for detection of anti-SARS-CoV-2 antibodies in 207 patients with COVID-19, 178 patients with serological evidence of different bacterial infections, 107 patients with confirmed viral respiratory disease, and 80 controls from the pre-COVID-19 era. In COVID-19 patients, the assays showed highest sensitivity in week 3 (Vircell-IgM/A and Euroimmun-IgA: 78.9% each) and after week 7 (Vircell-IgG: 97.9%; Euroimmun-IgG: 92.1%). The antibody indices were higher in patients with fatal disease. In general, IgM/IgA assays had only limited or no benefit over IgG assays. In patients with non-SARS-CoV-2 respiratory infections, IgG assays were more specific than IgM/IgA assays, and bacterial infections were associated with more false-positive results than viral infections. The specificities in bacterial and viral infections were 68.0 and 81.3% (Vircell-IgM/IgA), 84.8 and 96.3% (Euroimmun-IgA), 97.8 and 86.0% (Vircell-IgG), and 97.8 and 99.1% (Euroimmun-IgG), respectively. Sera from patients positive for antibodies against Mycoplasma pneumoniae , Chlamydia psittaci , and Legionella pneumophila yielded particularly high rates of unspecific false-positive results in the IgM/IgA assays, which was revealed by applying a highly specific flow-cytometric assay using HEK 293 T cells expressing the SARS-CoV-2 spike protein. Positive results obtained with anti-SARS-CoV-2 IgM/IgA ELISAs require careful interpretation, especially if there is evidence for prior bacterial respiratory infections.

Invasive Mycosis in Medical Intensive Care Unit Patients with Severe Alcoholic Hepatitis - Tobias Lahmer; Marlena Messer; Christiane Schwerdtfeger; Sebastian Rasch; Marcel Lee; Bernd Saugel; Roland M. Schmid; Wolfgang Huber (Mycopathologia, 2014)

Genetic variants in the RELN gene are associated with otosclerosis in multiple European populations - Isabelle Schrauwen; Megan Ealy; Erik Fransen; Kathleen Vanderstraeten; Melissa Thys; Nicole C. Meyer; Marcel Cosgarea; Alex Huber; Manuela Mazzoli; Markus Pfister; Richard J. H. Smith; Guy Van Camp (Human Genetics, 2010)

Mutations of the gene encoding the transmembrane transporter protein ABC-C6 cause pseudoxanthoma elasticum - Berthold Struk; Li Cai; Stéphanie Zäch; Wan Ji; Joon Chung; Amanda Lumsden; Markus Stumm; Marcel Huber; Lori Schaen; Chung-Ah Kim; Lowell A. Goldsmith; Denis Viljoen; et al. (Journal of Molecular Medicine, 2000)